FORMULATION OF A MULTICRITERIA PARTIALLY INTEGER DYNAMIC OPTIMIZATION PROBLEM - Ivchenko, Irina (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2021)
The problem of building of an integrated model of an enterprise, taking into account the main types of its activities, are prezented in the article. The key objective of the study is the formation of an integrated enterprise management system. The enterprise management system should be supported by mathematical models. The approach to the similar description of qualitatively different processes of enterprise functioning (production, innovation-investment and financial ones) are explained. The list of external and internal input and output parameters which  characterize the state of the enterprise at each time moment is given. The author suggests establishment of input-output dependence for a given economic object, using a set of technological time-varying coefficients. For this, control variables are foreseen in the model. Control variables will regulate the distribution of resources and fixed assets between all possible production technologies. This makes it possible to unambiguously determine both the costs of all factors of production for each technology at each time moment, and the volume of production. It’s also  possible to associate investment and innovation activities with production processes and with assets dynamics. Techniques for integrating technological modes within a complex dynamic partial-integer optimization model make it possible to generalize the tasks of distributing all factors of production and assets between production technologies and assets recovery and between all the stages of investment projects. Financial activity is considered as the activity of an enterprise, ensuring all the payments that are necessary for a given management strategy and operation mode. To determine the modes of the enterprise financial activity at each time moment, it is also proposed to enter control parameters into the model. The article also describes appropriate model constraints related to the implementation of all the types of activities. The choice of effective vectors of control variables values should be done by means of synchronization of the main types of economic and innovation-investment activities. The purpose of such a task is to find an effective management strategy for the enterprise. As goal functions in the multicriteria optimizing problem it is proposed to use time-integrated values of profit, costs and payback period.